Cranberry Juice and Combinations of Its Organic Acids Are Effective against Experimental Urinary Tract Infection - Jensen, Heidi D.; Struve, Carsten; Christensen, Søren B.; Krogfelt, Karen A. (Frontiers in Microbiology, 2017)
The antibacterial effect of cranberry juice and the organic acids therein on infection by uropathogenic Escherichia coli was studied in an experimental mouse model of urinary tract infection (UTI). Reduced bacterial counts were found in the bladder (P < 0.01) of mice drinking fresh cranberry juice. Commercially available cranberry juice cocktail also significantly reduced (P < 0.01) bacterial populations in the bladder, as did the hydrophilic fraction of cranberry juice (P < 0.05). Quinic, malic, shikimic, and citric acid, the preponderant organic acids in cranberry juice, were tested in combination and individually. The four organic acids also decreased bacterial levels in the bladder when administered together (P < 0.001), and so did the combination of malic plus citric acid (P < 0.01) and malic plus quinic acid (P < 0.05). The other tested combinations of the organic acids, and the acids administered singly, did not have any effect in the UTI model. Apparently, the antibacterial effect of the organic acids from cranberry juice on UTI can be obtained by administering a combination of malic acid and either citric or quinic acid. This study show for the first time that cranberry juice reduce E. coli colonization of the bladder in an experimental mouse model of urinary tract infection and that the organic acids are active agents.